Evolution of transnationalization of the world tourism business - Довгаль, Георгій (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
Transnationalization of international tourism is a consequence of globalization, which will provide not only the rapid growth of the competitiveness of the tourism product, but also receive a number of benefits on a global scale. The process of transnationalization tourism industry is multifactorial and has a pronounced stage of historical development, as well as the effects of the economic, political, social, managerial The author proved that the tourist business acquires the features of mass production after the Second World War, when the development of communication technologies and vehicles is increasing range of tourist offers. In addition, as a result of economies of scale of production and falling prices for transportation services significantly reduces the cost of travel as a result of competition in the sector. The article concludes that large enterprises are located on the transnational level of management in order to mitigate the weaknesses of the market and the elimination of barriers to free international trade in tourism services. Eliminated the differences in the economic, social, political, cultural and religious conditions of life; in taxation and foreign exchange controls; in the value of fixed factors of production, as well as maximized economies of scale as a way to gain competitive advantage.